Detection of Gastric Precancerous Conditions in Daily Clinical Practice: A Nationwide Survey. Issue 6 (18th September 2014) - Lahner, Edith; Zullo, Angelo; Hassan, Cesare; Perri, Francesco; Dinis‐Ribeiro, Mário; Esposito, Gianluca; Di Giulio, Emilio; Buscarini, Elisabetta; Bianco, Maria Antonietta; De Boni, Michele; Annibale, Bruno
Abstract: Background: The burden of gastric precancerous conditions and factors associated with their detection have not been fully investigated in community‐based settings. Little is known about adherence to Sydney system for histopathology of gastric biopsies. Objective: We aimed to investigate what really happens in clinical practice with regard to the detection of gastric atrophy and intestinal metaplasia in dyspeptic patients. Methods: We performed a nationwide survey of 979 consecutive patients (50–65 years old) with dyspeptic symptoms, examined at 24 gastrointestinal endoscopy units throughout Italy. Clinical information was collected from questionnaires; a standard bioptic mapping was performed in each unit, biopsies from each patient were analyzed by histopathology performed according to daily clinical practice in each local histopathology center. Results: Separate descriptions of antral and corporal biopsies were included in 679 pathology reports (69%), whereas Sydney system was applied in 324 reports (33%). Gastric atrophy without intestinal metaplasia (GA) and gastric atrophy with intestinal metaplasia (GIM) were detected in 322 (33%) patients. The full adherence to Sydney system significantly increased the probability of detecting GIM (OR 9.6, 95% CI 5.5–16.7), GA (OR 1.92, 95% CI 1.07–3.44), and either of the conditions (OR 6.67, 95% CI 4.36–10.19). Conclusions: This nationwide survey showed that in one‐third of dyspeptic patients, gastric precancerous conditions are detected. In daily routine practice, only 1/3 of histology reports were worked out adhering to Sydney system showing that international guidelines are poorly observed in clinical practice. This may represent a critical element for surveillance strategies for gastric cancer.